Selecting native entomopathogenic fungi against Cosmopolites sordidus (Germar) in the laboratory (Revista de Ciências Agroveterinárias, 2021)
The objective of this study was to select native isolates of entomopathogenic fungi against adult Cosmopolites sordidus in laboratory conditions. Four isolates of Beauveria bassiana, two isolates of Metarhizium anisopliae, and two isolates of Paecilomyces lilacinus were tested against C. sordidus. The entomopathogenic fungi that resulted in mortality rates over 50% were M. anisopliae (MA-CsCha and MA-Carabid) and B. bassiana (BB-CsCha and BB-CsLp). The most virulent isolates were MA-CsCha, BB-CsCha, and MA-Carabid with median lethal times (LT50) of 4.82, 5.4, and 5.79 days, respectively. In conclusion, the MA-CsCha, BB-CsCha, MA-Carabid, and BB-CsLp isolates are viable candidates to be tested in banana fields.
Keywords: Banana root borer; Beauveria bassiana; Metarhizium anisopliae; Biocontrol.